O processo de trabalho do terapeuta ocupacional na rede de saúde mental: focalizando a avaliação inicial - Gozzi, Alana de Paiva Nogueira Fornereto (2012)
Occupational therapy is constituted as a field of knowledge and service that makes use of human activities, such as a differentiated technology and public policy consistent with recent mental health. Currently, occupational therapy in the mental health field makes use of different benchmarks for the development of their practice, for which the main objectives are to broaden health care and the possibility of redemption citizenship rights of people with a mental disorder. Note the importance of verifying how occupational therapists that are inserted into the network of mental health services perform the assessment of user demands on their performance scenarios. The present study aimed to understand the forms of assessment used by occupational therapists in different equipment that make up the network of mental health services and to identify the admission criteria used by occupational therapists to users of mental health services. This is a descriptive cross-sectional case study, which made use of a qualitative approach. Data collection was through interviews with occupational therapists inserted in mental health services in a health region of a Regional Health Department of the State of São Paulo. Data analysis was performed using the method of thematic analysis, which allowed the identification of categories of analysis. The results showed that, in its entirety, the respondents are women, with service time between nine months and eighteen years. The network of services in the area chosen for the data collection relied on equipment ranging from basic care, such as the Center for Support Family Health (NASF) and minimum teams entered in basic health units, up clinics, psychosocial care center (CAPS) and psychiatric hospital. With respect to performing the initial assessment, the respondents include this point in the process of work as important to meet the user's needs and that the same demand. In most cases, the initial evaluation is conducted in informal format, with tools built by professionals in their own practices. People with chronic mental illnesses are admitted to occupational therapy services, mostly. It is expected that the study will help in the construction of technical criteria for admission from users of occupational therapy services in mental health, the expansion of knowledge and ideas about the practice of occupational therapists in mental health, as well as contributions to bring about forms initial assessment of the occupational therapist who works in the area of mental health.